Acceptance and Diffusion of Connected and Automated Driving in Japan and Germany - Eisenmann, Christine; Seibert, Dennis; Fleischer, Torsten; Taniguchi, Ayako; Oguchi, Takashi; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Springer, 2025)
This open access book gives comprehensive empirical insights on connected and automated driving (CAD) of road transport vehicles which leads to the driver being partially or completely replaced by automation. The current trend towards widespread research and development of automation of motorised individual transport is driven by the expected benefits, such as increased road safety, smoother traffic flow, reduction of congestion, or use of driving time for other activities. CAD has the potential to change several dimensions of the transport system, ranging from changes in car ownership to the availability of entirely new mobility services. Some proponents even expect CAD to revolutionise the current transport system as a whole. In order to make informed statements about the possible impact of CAD on transport systems, research must consider a wide range of open questions: In what way do the existing framework conditions of the prevailing mobility systems affect the impact of CAD? How does the governance style relate to regulatory changes and resource allocation in the development of CAD? Is an autonomous ride-hailing service really a profitable business case? What are the attitudes and expectations towards CAD in the general public? What are the effects of CAD on transport systems? What are other impacts of CAD that should be assessed? All of these questions were addressed within different projects as part of the Japanese-German Research Cooperation on CAD and can be discovered by the reader of this book.
Introduction -- Setting the Scene for Automated Mobility: A Comparative Introduction to the Mobility Systems in Germany and Japan -- Governance, Policy and Regulation in the Field of Automated Driving: A Focus on Japan and Germany -- Business Analysis and Prognosis Regarding the Shared Autonomous Vehicle Market in Germany -- Transportation Effects of Connected and Automated Driving in Germany -- Transportation Effects of CAD in Japan -- Overall Comparison Between Germany and Japan in Relation to Social Impact of Connected and Automated Driving.
Keywords: Automotive engineering; Transportation engineering; Traffic engineering; Automotive Engineering; Transportation Technology and Traffic Engineering